Genome-Wide and Exome-Capturing Sequencing of a Gamma-Ray-Induced Mutant Reveals Biased Variations in Common Wheat - Li, Yuting; Xiong, Hongchun; Zhang, Jiazi; Guo, Huijun; Zhou, Chunyun; Xie, Yongdun; Zhao, Linshu; Gu, Jiayu; Zhao, Shirong; Ding, Yuping; Fang, Zhengwu; Liu, Luxiang (Frontiers in Plant Science, 2022)
Induced mutagenesis is a powerful approach for the creation of novel germplasm as well as the improvement of agronomic traits. The evaluation of mutagenic effects and functional variations in crops are needed to facilitate mutation breeding. To investigate the mutagenic effects of gamma-ray irradiation in wheat, genomic variations of wheat early heading mutant (eh1) comparing to wildtype Zhongyuan 9 (ZY9) were characterized in this study. Whole genome re-sequencing of eh1 and ZY9 produced 737.7 Gb sequencing data and a total of 23537117 homozygous SNP and 1608468 Indel were identified. Analysis of SNP distribution across the chromosome suggested that mutation hotspot regions existed in certain part of chromosomes. Among the three subgenomes, the variation frequency in subgenome D was significantly lower than that of subgenome A and B. A total of 27.8 Gb data were obtained by exome-capturing sequencing and 217948 SNP and 13554 Indel were identified. Variation annotation in the exonic region showed that 5.0% of the SNP and 5.3% of the Indel were functionally important. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genome (KEGG) analysis suggested that genes with functional variation were enriched in several metabolic pathways including plant-pathogen interaction, protein processing in endoplasmic reticulum, and starch and sucrose metabolism. KASP genotyping with selected SNP within functional genes suggested that 85.7% of the SNP were polymorphic between the eh1 and wildtype. This study provided a basic understanding of the mechanism of gamma-ray irradiation in hexaploid wheat.